Bamboo Waste-based Bio-composite Substance: An application for Low-cost Construction Materials - Teodoro Astorga Amatosa; Michael E. Loretero (SPECTA Journal of Technology, 2020)
Bamboo is a lightweight and high-strength raw materials that encouraged researchers to investigate and explore, especially in the field of biocomposite and declared as one of the green-technology on the environment as fully accountable as eco-products. This research was to assess the technical feasibility of making single-layer experimental Medium-Density Particleboard panels from the bamboo waste of a three-year-old (Dendrocalamus asper). Waste materials were performed to produce composite materials using epoxy resin (C21H25C105) from a natural treatment by soaking with an average of pH 7.6 level of sea-water. Three different types of MDP produced, i.e., bamboo waste strip MDP (SMDP), bamboo waste chips MDP (CMDP) and bamboo waste mixed strip-chips MDP (MMDP) by following the same process. The experimental panels tested for their physical-mechanical properties according to the procedures defined by ASTM D1037-12. Conclusively, even the present study shows properties of MDP with higher and comparable to other composite materials; further research must be given better attention as potential substitute to be used as hardwood materials, especially in the production, design, and construction usage.